Disease burden and trends in gout for adolescents from 1990 to 2021, with projections to 2050 globally, in East Asia and China: results from the Global Burden of Disease study 2021 - Yang, Lu; Wang, Zhenyu; Cui, Ligang (Frontiers in Public Health, 2025)
BackgroundGout, a metabolic disorder driven by urate crystal deposition, has been understudied in adolescents, particularly in East Asia and China, where rising incidence aligns with rapid dietary and economic shifts. This study assessed the global, East Asian, and Chinese burden of adolescent gout from 1990 to 2021 and projected trends to 2050.MethodsUsing Global Burden of Disease (GBD) 2021 data, we analyzed incidence, prevalence, and disability-adjusted life years (DALYs) among adolescents aged 10–19 years. Age-standardized rates (ASRs) and estimated annual percentage changes (EAPC) were calculated. Autoregressive Integrated Moving Average (ARIMA) models projected future trends, while smoothing splines explored associations between sociodemographic index (SDI) and DALYs. Risk factor contributions were quantified by gender and region.ResultsFrom 1990 to 2021, global ASRs of incidence, prevalence, and DALYs rose annually by 0.26%, reaching 109.1, 653.8, and 20.2 per 100,000 in 2021, respectively. East Asia exhibited steeper increases (0.36–0.37% annually), with Taiwan (Province of China) reporting the highest ASRs (prevalence: 1,054.1; DALYs: 33.2 per 100,000). China saw 17.1–25.1% ASR increases, driven by metabolic risks (36.8%), obesity (31.4%), and kidney dysfunction (7.6%). Females consistently bore higher burdens than males across regions. An M-shaped SDI-DALYs relationship peaked at mid-high development levels (SDI ≈ 0.75). Projections indicated stable global trends but rising incidence and prevalence in East Asia and China by 2050.DiscussionThe escalating adolescent gout burden in East Asia and China reflects synergistic effects of obesity, metabolic syndrome, and lifestyle changes. Gender disparities highlight underrecognized risks in females. Sociodemographic transitions initially exacerbate then mitigate gout burden, emphasizing the need for early interventions targeting modifiable risks. Strengthening healthcare infrastructure and gender-specific prevention strategies are critical to curb projected increases in high-risk regions.